Analisis Akselerasi Pengembangan KDKMP Melalui Peran Pendamping di Kabupaten Ogan Komering Ulu - Resty Dwi Rahmah (J-Coop : Journal of Co-operative, 2026)
This study aims to analyze the role of facilitators in accelerating the development of the Red and White Village/Sub-district Cooperative (KDKMP) program in Ogan Komering Ulu using a qualitative methodology with a case study design. The results show that the KDKMP program in Ogan Komering Ulu Regency covers 157 villages/sub-districts and has received support from cooperative service officials, village officials, cooperative service officials, and KDKMP program administrators. A SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis was also used to collect data. However, the development of KDKMP still faces many challenges. These include limited business capital, low human resource capacity, uneven member participation, limited market access, low digital literacy, and suboptimal coordination between parties. Facilitators play a crucial role in assisting with administrative processes, legality, institutional strengthening, and operational oversight of cooperatives to ensure that governance runs clearly and according to procedures. Consequently, acceleration is needed through increased coordination between stakeholders, increased human resource capacity, digitalization of cooperatives, expansion of market access, and strengthening collaboration with various parties. It is hoped that this research will provide scientific contributions and practical suggestions for building cooperatives that depend on the economic empowerment of rural communities.